Optic flow contribution to locomotion adjustments in obstacle avoidance - Pinheiro Menuchi, Marcos Rodrigo Trindade; Bucken Gobbi, Lilian Teresa [UNESP] (Human Kinetics, 2012)
Locomotion generates a visual movement pattern characterized as optic flow. To explore how the locomotor adjustments are affected by this pattern, an experimental paradigm was developed to eliminate optic flow during obstacle avoidance. The aim was to investigate the contribution of optic flow in obstacle avoidance by using a stroboscopic lamp. Ten young adults walked on an 8m pathway and stepped over obstacles at two heights. Visual sampling was determined by a stroboscopic lamp (static and dynamic visual sampling). Three-dimensional kinematics data showed that the visual information about self-motion provided by the optic flow was crucial for estimating the distance from and the height of the obstacle. Participants presented conservative behavior for obstacle avoidance under experimental visual sampling conditions, which suggests that optic flow favors the coupling of vision to adaptive behavior for obstacle avoidance. © 2012 Human Kinetics, Inc.
Keywords: Locomotion; Movement information; Obstacle avoidance; Optic flow; Visual sampling